2022
DOI: 10.3390/jcm11154570
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Performance of Two Current-Generation Transcatheter Heart Valve Prostheses in Severely Calcified Aortic Valve Stenosis

Abstract: Background: Treatment of severely calcified aortic valve stenosis is associated with a higher rate of paravalvular leakage (PVL) and permanent pacemaker implantation (PPI). We hypothesized that the self-expanding transcatheter heart valve (THV) prostheses Evolut Pro (EPro) is comparable to the balloon-expandable Sapien 3 (S3) regarding hemodynamics, PPI, and clinical outcome in these patients. Methods: From 2014 to 2019, all patients with very severe calcification of the aortic valve who received an EPro or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Overall: A total of twenty-one studies 7 16 , 18 , 19 , 21 23 , 25 29 , 31 , 32 were included that assessed mortality. Our analysis found that the results were significant for BEV compared to SEV for overall mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall: A total of twenty-one studies 7 16 , 18 , 19 , 21 23 , 25 29 , 31 , 32 were included that assessed mortality. Our analysis found that the results were significant for BEV compared to SEV for overall mortality.…”
Section: Resultsmentioning
confidence: 99%
“…30 days: Fourteen studies 9 11 , 13 15 , 21 , 22 , 25 29 , 31 reported 30-day mortality as one of their outcomes. A significant statistical relationship was found, and our analysis revealed favorability towards the BEV arm (OR = 0.780; 95% CI: 0.673–0.905; P = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…19 A recent comparison of SE EVOLUT Pro and BE SAPIEN 3 demonstrated safety and high efficacy of both THVs in patients with severe AV calcification, with lower complication rates and higher PPM rates with BE SAPIEN 3. 20 Data are scarce, however, regarding a direct comparison of third-generation prosthesis systems in this specific anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,24,32,33 Numerous studies have described an association between severe AV calcification and detrimental hemodynamic properties such as the occurrence of relevant postinterventional PVL for SE devices. 7,15,19,20 The higher rate of relevant PVL…”
Section: Hemodynamic and Echocardiographic Outcomesmentioning
confidence: 99%
“…PPM occurs when the EOA of the prosthesis is too small according to the patient's body size [54,58]. SEV with the supra-annular valve position allows for a larger EOA, lower transvalvular gradients and, consequently less PPM, as compared with BEV, which is characterized by intra-annular position and thereby reduced EOA [59][60][61].…”
Section: Patients With Extreme Annulus Dimensions or Difficult Sizingmentioning
confidence: 99%